2015
DOI: 10.1002/jctb.4636
|View full text |Cite
|
Sign up to set email alerts
|

Water vapour adsorption by a coffee-based microporous carbon: effect on CO2capture

Abstract: BACKGROUND: Carbon materials are appealing adsorbents for postcombustion CO 2 capture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
(60 reference statements)
3
22
0
Order By: Relevance
“…Until now, different adsorbents have been investigated under this condition to verify their CO 2 adsorption performances in practical application. For instance, Plaza et al investigated the effect of water vapor on CO 2 adsorption of a coffee-based micro-porous carbon through breakthrough experiments [23]. It was shown that the adsorption of CO 2 was not hindered by H 2 O at short adsorption time and but the adsorption capacity would be reduced by the co-adsorption of H 2 O at long adsorption time.…”
Section: Introductionmentioning
confidence: 98%
“…Until now, different adsorbents have been investigated under this condition to verify their CO 2 adsorption performances in practical application. For instance, Plaza et al investigated the effect of water vapor on CO 2 adsorption of a coffee-based micro-porous carbon through breakthrough experiments [23]. It was shown that the adsorption of CO 2 was not hindered by H 2 O at short adsorption time and but the adsorption capacity would be reduced by the co-adsorption of H 2 O at long adsorption time.…”
Section: Introductionmentioning
confidence: 98%
“…The actual content of H 2 O in the gas to be decarbonized will depend on the process where it originates (for example, the flue gas leaving a wet desulfurization unit in a coal power plant will be nearly saturated with water vapor) and its temperature (the lower the temperature the lower will be the absolute content of water vapor). Therefore the effect of water vapor on CO 2 capture is an important issue that needs to be addressed [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] However, benchmarking analysis does not attempt to obtain general results in different situations, but the most accurate results in specific situations. According to previous literature, [ 36,40–51 ] current research on carbon capture is still focused on the laboratory scale. Therefore, the geometric structure of the adsorption bed and adsorbent performance are shown in Table 4 and the operating parameters of TSA system are shown in Table 5 .…”
Section: Case II Using a Self‐coded Modelmentioning
confidence: 99%